Developing critical thinking in the grade six fast learner through reading - Guinoo, Nieves Sy 1941-; Baldo, Trinidad C. (Quezon City College of Education, University of the Philippines Diliman, 1972)
This study analyzed the critical thinking process, determined what the critical thinking process is, identified the steps basic to the critical thinking process, and assessed the classroom techniques and activities that can be adopted to develop critical thinking skills in the Grade Six fast learner through Reading. Observations indicate that the teaching for the development of critical thinking is feasible through specific teaching techniques, classroom activities and exercises in Reading geared to the interests and abilities of fast learners.
Vita.
Thesis (Master of Arts in Teaching - Special Education : Giftedness)--University of the Philippines, Diliman.
Keywords: Critical thinking in children -- Philippines; Reading (Elementary) -- Philippines; Gifted children -- Philippines; Sixth grade (Education) -- Philippines